Anti-Proliferation Potential and Content of Fucoidan Extracted from Sporophyll of New Zealand Undaria pinnatifida - Mak, Wilfred; Wang, Sheng Kelvin; Liu, Tingting; Hamid, Nazimah; Li, Yan; Lu, Jun; White, William Lindsey (Frontiers in Nutrition, 2014)
Undaria pinnatifida is a species of brown seaweed known to contain rich amounts of fucoidan, a sulphated polysaccharide known to possess various biological activities. We isolated crude fucoidan (F0) from the sporophylls of U. pinnatifida grown in the Marlborough Sounds, New Zealand. Sulphate content, uronic acid content and molecular weight of F0 were 15.02%, 1.24% and >150 kDa, respectively. F0 was fractionated to yield three further fractions: F1, F2 and F3. Cytotoxicity of two major fractions was determined by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The algal fucoidans specifically suppressed the proliferation of three cancer cell lines with less cytotoxicity against the normal cells. Selective cytotoxicity could relate to the distinctive structures of each fucoidan fraction. Results from this study provide evidence that fucoidan, especially from U. pinnatifida grown in New Zealand, possesses great potential to be used as a functional food to reduce cancer risk or supplement cancer treatment.